Law and economics of the monetary union - Helmut Siekmann (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2011)
The European Monetary Union euro has done very well since its initiation. Price stability has been secured and the external value of the new currency is more than satisfactory. The confidence in it is also shown by its increasing use as a global reserve currency. It has been a stabilizing factor in the current crisis. The recent budgetary problems of some member states are principally not a problem of the Monetary Union. It is therefore in no way justified to speak of a Euro-crisis. It is true, however, that the Monetary Union restricts the number of possibilities for member states to solve their financial problems but it does not eliminate them entirely that outside help would have become indispensible. The purchase of debt instruments of member states in financial distress by the ECB is questionable from an economic, and more important, from a legal point of view. The longer the duration, the less legally justifiable is it. Financial support for member states in severe financial distress might be acceptable as a temporary crisis resolution mechanism. A permanent support mechanism needs a basis in the primary law of the EU. The treatment of the risk of sovereign debt in the legal framework for financial institutions urgently needs improvement. Especially the capital requirements for credit institutions have to be adjusted.
urn:nbn:de:hebis:30-115290
Keywords: 330